First Diagnostic Marine Reptile Remains from the Aalenian (Middle Jurassic): a New Ichthyosaur from Southwestern Germany - Maxwell, Erin E. (2012)
Background: The Middle Jurassic was a critical time in the evolutionary history of ichthyosaurs. During this time interval, the diverse, well-studied faunas of the Lower Jurassic were entirely replaced by ophthalmosaurids, a new group that arose sometime prior to the Aalenian-Bajocian boundary, and by the latest middle Jurassic comprised the only surviving group of ichthyosaurs. Thus, the Middle Jurassic Aalenian-Bathonian interval (176–165 million years ago) comprises the time frame during which ophthalmosaurids not only originated but also achieved taxonomic dominance. However, diagnostic ichthyosaur remains have been described previously from only a single locality from this interval, from the Bajocian of Argentina. Methodology/Principal Findings: In this paper, we describe a new species of ichthyosaur, based on a partial articulated specimen from the Middle Jurassic of southwestern Germany. This specimen was recovered from the Opalinuston Formation (early Aalenian) and is referable to Stenopterygius aaleniensis sp. nov. based on features of the skull and forefin. The genus Stenopterygius is diverse and abundant in the Lower Jurassic of Europe, but its presence has not previously been confirmed in younger (Middle Jurassic) rocks from the northern hemisphere. Conclusions/Significance: This specimen represents the only diagnostic ichthyosaur remains reported from the Aalenian. It bears numerous similarities in size and in morphology to the Lower Jurassic species of the genus Stenopterygius and provides additional evidence that the major ecological changes hypothesized to have occurred at the end of the Toarcian took place sometime after this point and most likely did not occur suddenly. There is currently no evidence for the presence of ophthalmosaurids in the northern hemisphere during the Aalenian-Bathonian interval.